Improved Speaking Skills Through Application of the Role Playing Method in Grade VII Students of SMP Negeri Satu Atap 3 Dusun Hilir - Angely, Pier; Efendi, Anwar; Nurhidayah, Nurhidayah (CV. Media Digital Publikasi Indonesia, 2026)
This is a Classroom Action Research (CAR) aimed at enhancing the speaking skills of seventh-grade students at SMP Negeri Satu Atap 3 Dusun Hilir through the implementation of the Role Play method. The background of the study is based on the students' low speaking abilities, which are evident from their shyness, lack of self-confidence, flat intonation, unclear pronunciation, and limited vocabulary. Initial observations revealed that only 25% of the students met the Minimum Completeness Criteria (KKM) of 70, with an average score of 64.63. This situation indicates the necessity for the application of active learning strategies that provide students with opportunities to practice speaking in a pleasant environment. The study is a PTK study that is carried out in two phases and uses the Kemmis and McTaggart design models, conducted over two cycles. Each cycle includes stages of planning, action implementation, observation, and reflection. The subjects of the study consisted of eight students (5 males and 3 females). Data collection techniques involved observation, speaking ability tests, interviews, and photographic documentation. The assessment instruments covered six aspects: pronunciation, intonation, vocabulary, sentence structure, expression, and courage, with a scoring range of 1–4. Data analysis was performed using both quantitative and qualitative descriptive approach-es, with validity tested through source and technique triangulation. The results of the study indicate that the Role Play method is effective in improving students' speaking abilities. The average score increased from 64.63 (pre-cycle) to 70.63 (cycle I) and 77.38 (cycle II). The percentage of learning completeness also rose from 25% to 62.5%, and then further increased to 87.5%. Qualitatively, students became more courageous, confident, expressive, and capable of using good intonation and pronunciation. Learning activities became more vibrant, collaborative, and aligned with the dimensions of the Pancasila Student Profile. Therefore, it can be concluded that the implementation of the Role Play method is a strategic approach to enhance students' speaking skills.